Mādhavanidhana hẽ aitihāsika nāṭaka : Kādambarīsaṅgraha māsikapustamālepaikī - Bhāgavata, Ananta Nārāyaṇa (SAMP early 20th-century Indian books project, 1900)
On the death of Madhu Rao I, Peshwa, 1744?-1772, Maratha ruler.